Mutation of ARHGAP9 in patients with coronary spastic angina - Takefuji, Mikito; Asano, Hiroyuki; Mori, Kazutaka; Amano, Mutsuki; Kato, Katsuhiro; Watanabe, Takashi; Morita, Yasuhiro; Katsumi, Akira; Itoh, Toshiki; Takenawa, Tadaomi; Hirashiki, Akihiro; Izawa, Hideo; et al. (Journal of human genetics, 2010)
Coronary artery spasm has an important function in the etiology of variant angina and other acute coronary syndromes. Abnormal activation of Rho-family GTPases has been observed in cardiovascular disorders, but the function of genetic variability in Rho-family GTPases remains to be evaluated in cardiovascular disorders. We examined the genetic variability of Rho-family GTPases and their regulators in coronary artery spasm. We performed a comprehensive candidate gene analysis of 67 single nucleotide polymorphisms with amino-acid substitution in Rho-family GTPases and their regulators in 103 unrelated Japanese patients with acetylcholine-induced coronary artery spasm and 102 control Japanese subjects without acetylcholine-induced coronary artery spasm. We noted an association of the single nucleotide polymorphism of ARHGAP9 (rs11544238, Ala370Ser) with coronary artery spasm (odds ratio =2.67). We found that ARHGAP9 inactivated Rac as RacGAP and that the mRNA level of ARHGAP9 was strongly detected in hematopoietic cells. ARHGAP9 negatively regulated cell migration. The Ala370Ser polymorphism counteracted ARHGAP9-reduced cell migration, spreading and adhesion. The Ala370Ser polymorphism in the ARHGAP9 gene is associated with coronary artery spasm. These data suggest that the polymorphism of ARHGAP9 has a critical function in the infiltration of hematopoietic cells into the endothelium and inflammation leading to endothelial dysfunction.